2001
DOI: 10.1002/dev.1034
|View full text |Cite
|
Sign up to set email alerts
|

Stability of coupled fluctuations in movement and visual attention in infants

Abstract: Fluctuations in body movement and visual inspection were measured over minutes in 3-month-old infants to look for evidence of coupling. In Experiment 1, infants (n 12) looked ad libitum at two identical pictures for an average of 7.3 min. Analysis of the spontaneous¯uctuations in movement and inspection revealed that they were inversely coupled: Moment-to-moment changes in movement and inspection occurred in opposite directions. In Experiment 2, after 4 min of free looking, infants (n 33) were presented with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…LabVIEW v.7.1 software (National Instruments, Austin, TX) was used to integrate body movement measures to 10 Hz and conduct movement analyses. Similar procedures are reported in Bacher and Robertson (2001).…”
Section: Measurementssupporting
confidence: 81%
See 2 more Smart Citations
“…LabVIEW v.7.1 software (National Instruments, Austin, TX) was used to integrate body movement measures to 10 Hz and conduct movement analyses. Similar procedures are reported in Bacher and Robertson (2001).…”
Section: Measurementssupporting
confidence: 81%
“…The infants exhibited orienting responses to both kinds of stimuli as expected: number of eye movements decreased, body movement decreased, and heart rate slowed (Bacher & Robertson, 2001;Malcuit, Pomerleau, & Brosseau, 1988;Richards, 1988). This pattern was apparent in the moving object condition and the social condition, but the magnitude of changes in body movement (and heart rate) was more dramatic in the moving object condition.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Results revealed that, like the presence of visual information, directed attention also interferes with infants’ movement; infants moved more when they did not direct attention toward the monitor (no attention, M = 2.00, SD = .19; attention, M = 1.79, SD = .30; t (45) = 5.84, p (two-tailed) < .001). This result is consistent with those obtained by Bacher and Robertson (2001), who found that visual attention and movement were inversely related in three-month-old infants.…”
Section: Resultssupporting
confidence: 93%
“…The first two minutes was sufficient to analyze the typical rate of changes in gaze for infants given that many such movements may be sampled during that period of time. Also, although patterns of attention fluctuate over time and transient patterns occur in new environments 35, a two min period of observation in a stable environment extends well beyond the period of these fluctuations. A time sampling approach was used to estimate the frequency of gaze shifts.…”
Section: Methodsmentioning
confidence: 99%